2022
DOI: 10.1021/acs.est.1c06180
|View full text |Cite
|
Sign up to set email alerts
|

Absorption Enhancement of Black Carbon Aerosols Constrained by Mixing-State Heterogeneity

Abstract: Atmospheric black carbon (BC) has a large yet highly uncertain contribution to global warming. When mixed with non-BC/coating material during atmospheric aging, the BC light absorption can be enhanced through the lensing effect. Laboratory and modeling studies have consistently found strong BC absorption enhancement, while the results in ambient measurements are conflicting, with some reporting weak absorption enhancement even for particles with large bulk coating amounts. Here, from our direct field observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…During the sampling time, a bimodal distribution of SF , which was defined as the ratio of uncoated particle size ( d c ) distribution after heating at 300 o C to the selected size ( d p ) of unheated particles, was observed (Figures 2a and 2b). The bimodal SF distribution implies heterogeneously distributed coating material across the particle population (Zhai et al., 2022). We attribute the two SF modes to two distinct sources: the local traffic emissions from urban Shanghai, which were dominated by the baerly or thinly coated BC particles (i.e., Mode 1), and the long‐range transport air masses from northern China that passed across the densely coal‐burning and industrial areas, taking along BC‐containing particles that are deeply aged with thick coatings (i.e., Mode 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…During the sampling time, a bimodal distribution of SF , which was defined as the ratio of uncoated particle size ( d c ) distribution after heating at 300 o C to the selected size ( d p ) of unheated particles, was observed (Figures 2a and 2b). The bimodal SF distribution implies heterogeneously distributed coating material across the particle population (Zhai et al., 2022). We attribute the two SF modes to two distinct sources: the local traffic emissions from urban Shanghai, which were dominated by the baerly or thinly coated BC particles (i.e., Mode 1), and the long‐range transport air masses from northern China that passed across the densely coal‐burning and industrial areas, taking along BC‐containing particles that are deeply aged with thick coatings (i.e., Mode 2).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a particle‐resolved method to predict the E abs was developed by considering the distribution of BC coating thickness, which could successfully predict the E abs consistent with the observations (Zhai et al., 2022). In the current study, the same data set was considered and we extended the previous work to a case study that focused on the relationship between particle aging and the E abs .…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…The evolution of BC at the level of single particles however raises more complexity as ambient BC contains a range of morphologies, and this could have large spatiotemporal variation. Recent studies using combined field work still found large discrepancies even at the same coating/rBC ratio. , This may be explained by the heterogenicity of particles when the coatings are distributed to a range of individual BC particles in bulk. To identify the population of single BC in bulk for which the core–shell microstructure should be applied (hereby E abs exists) or not is important to estimate the overall absorbing properties. Previous studies identified a transition regime of BC where hybrid optical models (Mie core–shell approach or without E abs ) should be applied, which corresponded with a coating/rBC mass ratio between 1 and 3 or at other ratio ranges depending on environments .…”
Section: Introductionmentioning
confidence: 99%